Information Channels and Narratives: To Vaccinate or Not to Vaccinate, That is the Question (Altre Modernità, 2022)
The discourses surrounding the COVID-19 vaccination are extensive and have been prolific over the last eighteen months. There has been particular debate among groups of vaccinated and non-vaccinated individuals discussing health benefits and a sense of civic duty in order to protect oneself and those around us as well as considering the extent to which a state really can oblige citizens to uptake the vaccine through a vaccination mandate.This study investigated the discourses regarding choosing to undergo the SARS-CoV-2 vaccination or otherwise and how these discourses are framed within the global and Italian contexts. The role of information channels, including the media, was also investigated along with the power balances revealed among the vaccinated and non-vaccinated individuals’ discourses. An online ethnographic poll was designed and distributed through online channels and follow up focus groups using semi-structured interviews were recorded for transcription and linguistic analysis. Results show some interesting linguistic findings regarding potential discrimination due to the vaccination pass mandate along with the narratives that surround these.
Keywords: Pandemic; Discourse Analysis; COVID-19 Vaccinations; Vaccine Narratives